Rivalitas Tradisi Modernitas dalam Perspektif Poskolonial: Telaah atas Sejumlah Sajak Abad 20 - Suyono Suyatno (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2012)
Since modernity go to Indonesia along with the application of ethical politics of the Dutch colonial government, it can be said of conflict and rivalry between tradition and modernity in this country. A number of poems written in the early to late 20th century reflected the rivalry between tradition and modernity is. With the postcolonial approach is expected to be seen who the party is dominant and the marginalized in the rivalry between tradition and modernity in this country, as reflected in a number of poems.